O excesso de acolhimentos em instituições de acolhimento de crianças e adolescentes na pandemia da COVID-19 e os impactos no trabalho do/a assistente social - Stevens, Tassiane da Silva Oliveira (My University, 2022)
The present study represents the critical reflective learning process for the completion of the Social Service Course at the University of Caxias do Sul. This study is the result of research that takes place in a pandemic moment in which the Supervised Internship in Social Work I, II and III took place, from 2021 to the first half of 2022. Its research problem is the following question: How Did the Institutional Shelter Services for children and adolescents deal with the excess of shelters that occurred during the COVID-19 pandemic and what were the impacts on the technical work of the social worker? In order to contemplate the proposed problem in an organized and satisfactory manner, the following guiding questions were listed: 1 – What is and how is an institutional reception service for children and adolescents organized in Brazil? 2 – How is the Social Assistance Policy organized in Brazil? What are your guidelines? 3 – How was the Social Assistance Policy organized to meet the demand imposed by the COVID-19 pandemic in the country? 4 – Have there been changes in relation to the factors that motivated the receptions in the pandemic in relation to the previous ones? 5 – How does Social Service work in a shelter institution for children and adolescents? What changes have occurred in the work of the social worker with the COVID-19 pandemic? 6 – What was sought to be done to qualify the work of Social Work in the institutional space to respond to the demand for work? The main objective of this study was to identify, describe and discuss, through documental, bibliographical and survey analysis, the work of social workers in Institutional Sheltering Services for Children and Adolescents in the context of the COVID-19 pandemic in Brazil. To understand the social reality, the critical dialectical materialist method was used, valuing the categories: historicity, totality, contradiction, mediation, work and everyday life. Regarding the approach, a quali-quantitative or mixed approach was used, within the investigative parameters that are typical of research conducted in the social field. Data collection was carried out through bibliographical, documentary and survey research, with the aim of carrying out comparative analyzes between the results already consolidated by official bodies of applied research. As the importance of this study, the sharpening of the expressions of the social issue that the pandemic emphasized was highlighted, leading to important changes in the professional work of workers in the Unified Social Assistance System - SUAS, and also in terms of the ethical commitment of social workers to offer a qualified service to users of this policy. As a result, the precariousness that the Public Social Assistance Policy has been suffering and the impact on the work of the Social Worker in the face of the excessive reception of children and adolescents during the pandemic, which directly impacted on the qualified service to users, reinforcing practices welfarists, historically known. Also, the need for investment in research was highlighted to analyze the impacts on the work of professionals, seeking, through bodies such as ABEPSS and CFESS, to apprehend in depth the impacts of this period on the work of Social Workers. [resumo fornecido pelo autor]
O presente estudo representa o processo de aprendizagem reflexivo crítico para a conclusão do Curso de Serviço Social da Universidade de Caxias do Sul. Este estudo é fruto de uma pesquisa que ascende em um momento pandêmico em que ocorreu o Estágio Supervisionado em Serviço Social I, II e III, no período do ano de 2021 ao primeiro semestre de 2022. Tem como problema de pesquisa o seguinte questionamento: Como os Serviços de Acolhimento Institucional para crianças e adolescentes lidaram com o excesso de acolhimentos ocorridos durante a pandemia da COVID-19 e quais os impactos no trabalho técnico do/a assistente social? Para contemplar de forma organizada e satisfatória, o problema proposto, foram elencadas as seguintes questões norteadoras: 1 – O que é e como se organiza um serviço de acolhimento institucional para crianças e adolescentes no Brasil? 2 – Como a Política da Assistência Social se organiza no Brasil? Quais são as suas diretrizes? 3 – Como a Política da Assistência Social se organizou para atender a demanda imposta pela pandemia da COVID-19 no país? 4 – Houve mudanças em relação aos fatores que motivaram os acolhimentos na pandemia em relação aos anteriores? 5 – Como se dá o trabalho do Serviço Social em uma instituição de acolhimento para crianças e adolescentes? Quais as mudanças que ocorreram no trabalho do/a assistente social com a pandemia da COVID-19? 6 – O que se buscou realizar para qualificar o trabalho do Serviço Social no espaço institucional para responder a demanda de trabalho? O objetivo principal deste estudo foi identificar, descrever e discutir, mediante análise documental, bibliográfica e de levantamento, o trabalho do/a assistentes sociais nos Serviços de Acolhimento Institucional para Crianças e Adolescentes no contexto da pandemia da COVID-19 no Brasil. Para a compreensão da realidade social foi utilizado o método materialista dialético crítico, valorizando as categorias: historicidade, totalidade, contradição, mediação, trabalho e cotidianidade. Com relação a abordagem, utilizou-se o enfoque quali-quantitativo ou misto, dentro dos parâmetros investigativos que são próprios de uma pesquisa conduzida no campo social. A coleta de dados se deu por meio de pesquisa bibliográfica, documental e de levantamento, com o intuito de realizar análises comparativas entre os resultados já consolidados por órgãos oficiais de pesquisa aplicada. Como importância deste estudo, destacou-se a agudização das expressões da questão social que a pandemia enfatizou, acarretando alterações importantes no trabalho profissional dos trabalhadores do Sistema Único de Assistência Social - SUAS, e também quanto ao compromisso ético dos/as assistentes sociais em ofertar um serviço qualificado aos usuários desta política. Como resultados, evidenciou-se a precarização que a Política Pública de Assistência Social vem sofrendo e o impacto no trabalho do/a assistente social diante do excesso de acolhimentos de crianças e adolescentes durante a pandemia, o que impactou diretamente no atendimento qualificado aos usuários, reforçando práticas assistencialistas, historicamente conhecidas. Ainda, destacou-se a necessidade de investimento em pesquisas para analisar os impactos no trabalho dos profissionais, buscando, por meio de órgãos como a ABEPSS e o CFESS, apreender de forma aprofundada os impactos deste período no trabalho dos/as Assistentes Sociais. [resumo fornecido pelo autor]
Keywords: Serviço social; COVID-19; Pandemias - Aspectos sociais